Nail changes caused by chemotherapy among cancer patients: A cross-sectional study of northwest rajasthan - Madhvi Trivedi; R D Mehta; H S Kumar; B C Ghiya; Prasoon Soni; Manish Kumar Meena; Vineet Kumar; S Rekha (Wolters Kluwer Medknow Publications, 2020)
Background: The nail changes caused by chemotherapy in cancer patients are difficult to assess and often overlooked by clinician. The present study was undertaken to study nail changes caused by various chemotherapeutic agents and various drug protocols most commonly associated with them. Materials and Method: Five hundred patients with malignancies receiving chemotherapy in the oncology ward and skin outpatient department were screened in this cross-sectional observational study from November 2018 to October 2019. Results: Nail changes due to chemotherapy were observed in 37.6% patients. The most common condition observed was melanonychia (84.04%), followed by half and half nails (6.91%), erythronychia (5.31%), longitudinal grooves (2.12%), leukonychia (2.12%), Mees' lines (1.59%), Beau's lines (0.53%), pitting (0.53%), and subungual hyperkeratosis (0.53%). The usual protocol to cause melanonychia was platinum analogues + taxanes based combinations, half and half nails by platinum analogues + taxanes + 5 fluorouracil (5FU) based polypharmacy, and erythronychia by cisplatin-based adjuvants. Conclusion: The knowledge of the nail changes caused by chemotherapy will help in counseling of already worried patients with malignancy. It will also improve patient compliance and enrich the clinicians' knowledge pertaining to chemotherapy-induced nail changes.